The Urgency of Reformulating Bali's Regional Tourism Policy to Prevent Environmental Damage and the Erosion of Local Wisdom (Contrarius Series: Law & Social Justice, 2026)
This study aims to analyze the urgency of reformulating tourism policy in Bali in order to address environmental damage and the erosion of local culture. The mass tourism development model that has been implemented thus far has proven to have negative effects, such as infrastructure overcapacity, ecosystem degradation, and the commodification of sacred values. Using normative legal research methods, this study examines laws and regulations related to sustainable tourism and cultural preservation. The results show a gap between regulations and implementation that requires a review of the basic principles of tourism policy. Reformulation must emphasize tourism based on the values of Tri Hita Karana, limit quantity, improve quality, and involve the active participation of local communities in management and supervision.